2020
DOI: 10.1111/bcpt.13482
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐state pharmacokinetic and pharmacodynamic profiling of colistin in critically ill patients with multi‐drug–resistant gram‐negative bacterial infections, along with differences in clinical, microbiological and safety outcome

Abstract: Limited data are present regarding the steady-state pharmacokinetics and pharmacodynamics of colistin in critically ill patients suffering from multi-drug-resistant gram-negative bacterial (MDR-GNB) infections. We aimed to profile the steady-state pharmacokinetics and pharmacodynamics of colistin in critically ill patients with MDR-GNB infections, along with determining the predictors that could influence the clinical, microbiological and safety outcome. We recruited 30 critically ill patients suffering from M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…The V d value of colistin in critically ill patients in the Grégoire et al [11] study was consistent with the distribution in healthy volunteers [11,33], which did not represent the pathophysiological changes that occur in critically ill patients. Karaiskos et al [3] also observed a lower V d value (80.4 L) compared with earlier studies [4,6,10]. This was due to the volume of colistin being dependent on the available fraction of the A plus B form [3].…”
Section: Volume Of Distribution (V D ) Of Cms and Colistinmentioning
confidence: 74%
See 4 more Smart Citations
“…The V d value of colistin in critically ill patients in the Grégoire et al [11] study was consistent with the distribution in healthy volunteers [11,33], which did not represent the pathophysiological changes that occur in critically ill patients. Karaiskos et al [3] also observed a lower V d value (80.4 L) compared with earlier studies [4,6,10]. This was due to the volume of colistin being dependent on the available fraction of the A plus B form [3].…”
Section: Volume Of Distribution (V D ) Of Cms and Colistinmentioning
confidence: 74%
“…Colistin’s pharmacokinetics and clinical application have been studied extensively in the past. Unfortunately, studies have found inter- and intra-individual variability in the pharmacokinetics of colistin, resulting in extremely varied plasma concentrations following the same dosage schedule [ 2 , 3 , 4 , 5 ]. In vivo, CMS has complex pharmacokinetics and variable bioconversion, particularly in patients with varying degrees of renal function [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations